Posted by **Tara** on Saturday, January 9, 2010 at 10:40am.

4tan^2u-1=tan^2u

3tan^2u=1

tan^2u=1/3

sq. root of (tan^2u)=sq. root of (1/3)

tanu=sq. root of (3)/3

tanu=sq. root of 1

Did I do this one right? If not, could you please show me the correct method??

Thanks!

## Answer this Question

## Related Questions

- Trig. - sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times...
- calculus - Show that tan^3(x)-8(tan^2(x))+17(tan(x)0-8 = 0 has a root in [0.5, 0...
- math - tan (u-v) given sin u=3/4 and cos v= -5/13 with U and V in quadrant 2 Use...
- trig - Given that tan 45=1, use tan(x+y) to show that tan 22.5= /2 - 1. (/is ...
- mathematics - 1.)Sin^-1(x)+Sin^-1(y)+Sin^-1(z)= pie Prove that X.root(1-y^2)+y....
- maths surds please help and explain - Simplify A.1/root a +2 b.root 18/25 c.root...
- Calc - y= cube root (1+tan(t)) OR y= (1+tan(t))^(1/3) The answer I got was y'= (...
- Algebra II - Multiple Choice (theta) means the symbol 0 with the dash in it. 1.)...
- math - Use the exact values of the sin, cos and tan of pi/3 and pi/6, and the ...
- Algebra - I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1...